1992
DOI: 10.1017/s0021859600070726
|View full text |Cite
|
Sign up to set email alerts
|

Early venison production from red deer (Cervus elaphus) as affected by grazing perennial or annual ryegrass pastures, pasture surface height and immunization against melatonin

Abstract: S U M M A R YTwo grazing experiments in New Zealand, using newly weaned red deer stags, assessed methods of maximizing growth over winter and spring, with the objective of attaining a slaughter weight of 92 kg liveweight (> 50 kg carcass) at the end of spring, by 12 months of age. Perennial ryegrass/white clover pastures, and the same direct-drilled with an annual ryegrass, were grazed at two surface heights (5 cm and 10cm; Experiment 1; 1988) or at similar pasture mass (Experiment 2; 1989). Balanced groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
6
11
0
Order By: Relevance
“…The present study confirmed that when relying entirely on perennial ryegrass/white clover pasture for 12 month venison production, a low proportion of deer reached target slaughter LW (92 kg or greater) and carcass weights barely attained 50 kg, supporting earlier observations (Ataja et al 1992;Semiadi et al 1993). It also showed that spiker velvet antler production was low (0.2 kg/stag).…”
Section: Discussionsupporting
confidence: 91%
“…The present study confirmed that when relying entirely on perennial ryegrass/white clover pasture for 12 month venison production, a low proportion of deer reached target slaughter LW (92 kg or greater) and carcass weights barely attained 50 kg, supporting earlier observations (Ataja et al 1992;Semiadi et al 1993). It also showed that spiker velvet antler production was low (0.2 kg/stag).…”
Section: Discussionsupporting
confidence: 91%
“…The weaner red deer showed intermediate growth during autumn, slow growth during winter, and high growth during spring in the present experiment, in agreement with the growth of farmed red deer being seasonal (Blaxter et al 1974;Drew 1976;Fennessy et al 1981;Ataja et al 1992;Semiadi et al 1993). Slow growth of the animals during winter is typical for young red deer, because of the seasonal loss of appetite (Kay 1985;Barry et al 1991), and acts as a major constraint to increasing venison production from young deer.…”
Section: Seasonal Liveweight Changessupporting
confidence: 89%
“…This resulted in high growth rates and the proportion of animals attaining target slaughter weight was an improvement on the findings of Ataja et al (1992) (41%) and Semiadi et al (1993) (75%) for young red deer stags grazing perennial ryegrass/white clover pastures (Table 7).…”
Section: Seasonal Liveweight Changesmentioning
confidence: 80%
See 2 more Smart Citations